Technology, work organisation and job quality in the service sector: an introduction - Connell, Julia; Gough, R.; McDonnell, A.; Burgess, John (Routledge, 2014)
This special issue volume is concerned with how technology is changing the nature of work and working conditions while generating new products and new forms of service delivery. The five articles included in this volume cover service work, from the routine and clerical through to highly credentialed and professional work. Although some of the established challenges concerning the impact of Information and Communication Technology (ICT) on work and workplaces are evident in the articles, it is also clear that new service delivery processes demand new skills and training to some extent. Overall findings indicate that while ICT competencies are important, they need to be supplemented by the soft skills that are crucial for effective customer interactions and more open work systems with greater autonomy and participation whereby flexible work teams can have a positive impact on job quality outcomes. This introductory article examines technology and the changing nature of work through three strands of interpretation, prior to introducing the five articles in this special issue.